Evolutionary Perspective in Rickets and Vitamin D - Hochberg, Ze'ev; Hochberg, Irit (Frontiers in Endocrinology, 2019)
Modern lifestyle limits our exposure to sunlight, which photosynthesizes vitamin D in the skin, and the incidence of nutritional rickets has been resurging. Vitamin D is one of the oldest hormones; it is photosynthesized in all forms of life from the phytoplankton to mammals. A selective sweep of the promoter of the vitamin D receptor (VDR) happened as soon as Homo sapiens migrated out of Africa; it co-adapted with skin color genes to provide a fine-scale adaptation to latitudes and the levels of exposure to ultraviolet (UV)B radiation along the route out of Africa. Exposure to UVB radiation balances the need for vitamin D photosynthesis and degradation of folic acid by UVB radiation. Skin color follows a latitude distribution: the darkest populations inhabit the tropical belt; and the fair-skinned populations inhabit the northern countries. Due to their greater need for calcium during their reproductive life, the skin color of women is lighter- than that of men. Vitamin D is essential for mineral homeostasis and has a wide variety of non-skeletal functions, of which the most important for natural selection is a regulatory function in the innate immune system. In the human fossil record, vitamin D deficiency coincided with bone tuberculosis. About 6000 years ago, a diet which included cow's milk provided Neolithic humans with twice as much calcium and was more alkaline than that of its Paleolithic predecessors. Adiposity is negatively associated with the vitamin D status and obese individuals require 2–3 times more vitamin D than non-obese individuals to normalize circulating 25OHD levels. In an era of an obesity epidemic, we need more research to determine whether adiposity should be taken into account when determining the dietary requirements for vitamin D and calcium and the optimal serum 25OHD levels.